STRATEGI KOMUNIKASI INTERPERSONAL SALES DAN MARKETING DALAM MENINGKATKAN MINAT PELANGGAN DI HOLIDAY INN RESORT BALI BENOA - Desak Putu Oka Shinta Purnamayanti; I Gusti Ngurah Sudiana; I Gede Januariawan (Anubhava: Jurnal Ilmu Komunikasi HIndu, 2021)
Based on data from the Central Bureau of Statistics Bali Province in 2020 there was a decrease in the number of room occupancy in 5-star hotels, especially in Badung Regency. This is a challenge for a new five-star hotel that was established in 2015, namely the Holiday Inn Resort Bali Benoa. To increase customer visits, an interpersonal communication strategy is needed to attract customer interest and get feedback from customers. There are three problems in this research as follows: (1) How interpersonal sales and marketing communication strategies in attracting customers of Holiday Inn Resort Bali Benoa; (2) How is Holiday Inn Resort Bali Benoa customer feedback; (3) What are the advantages and disadvantages of sales and marketing of Holiday Inn Resort Bali Benoa. Theories used are communication planning theory, uncertainty reduction theory, and marketing communication theory. Data collection techniques were carried out by observation, interviews, and documentation. The technique of presenting data using qualitative descriptive. The results of this research are the interpersonal communication strategy of sales marketing, the need to determine goals, namely increasing visits, by planning and preparing offers such as paying attention to language selection, to offer products using media such as telephone, email, and social media to find customers. Reducing uncertainty for customers, sales marketing applies passive, active, and interactive strategies so that when a customer has visited the hotel, the hotel gets feedback through reviews available on the Website and online services. To support the increase in customers, marketing gives the offers by advertising, sales promotion, public relations and publicity, and personal selling. The advantages of this marketing are that it has detailed and communicative services and the weakness is in several offer still expensive and less negotiable offers